Orthodontic, Maxillofacial Surgery, and Prosthodontic Rehabilitation Supported by Miniscrew in a Patient with Cleft Lip and Palate - Alberto De Stefani; Giovanni Bruno; Martina Barone; Antonio Gracco (Hindawi Limited, 2021)
Aim. This paper is aimed at reporting the clinical case of a patient with cleft lip and palate treated with a multidisciplinary approach. Case Report. An 11-year-old patient presented cleft lip and palate, with persistent oronasal communication, tooth displacement, and upper and lower crowding with a deep curve of Spee. He was treated with metal bracket orthodontic therapy, graft surgery, and prosthetic rehabilitation supported by miniscrews. Conclusions. Cleft lip and/or palate patients require adequate management of the case to resolve the anomalies connected to their condition and to improve their quality of life.